[Ulotka z wezwaniem do strajku 28 lutego 1985 r.] . Flier with a call to strike on 28 February 1985 - Tymczasowa Komisja Koordynacyjna NSZZ "Solidarność". (Tymczasowa Komisja Koordynacyjna NSZZ "Solidarność", 1985)
Red print on white paper. The flier contains text of an announcement issued by the Interim Coordinating Commission of Solidarity, which calls for a 15 min. strike on 28 February 1985 against price hikes and violation of the right to eight-hour workday.